Margherita Cannavacciuolo, Miradas en vilo. La narrativa de José Emilio Pacheco. Pról. de Eduardo Ramos-Izquierdo. Beatriz Viterbo, Rosario, 2014; 208 pp. - Ortiz López, Dante (El Colegio de México, 2017)
Se reseñó el libro: Miradas en vilo. La narrativa de José Emilio Pacheco.